Linguistic Means of Expression in Russian and Uzbek Riddles: A Comparative Analysis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Riddles, as ancient forms of oral folk art, encapsulate cultural values, environmental knowledge, and worldview across civilizations.Russian and Uzbek riddles, though structurally similar in their use of metaphor and poetic devices, reveal distinct cultural and ecological imagery reflective of Orthodox and Islamic influences respectively.Despite a rich body of folkloric literature, comparative linguocultural analysis of riddles between these two traditions has been limited, especially in examining symbolic representation and worldview expression.This study aims to compare the linguistic means of expression in Russian and Uzbek riddles, focusing on how each tradition encodes cultural identity, environmental interaction, and moral values.The analysis of 320 riddles demonstrates that Russian riddles favor symbols such as snow, forest, and stove—connoting isolation, endurance, and warmth—while Uzbek riddles prioritize sun, bread, and tandir—emphasizing community, sustenance, and harmony. Russian riddles lean toward lyrical structures, while Uzbek riddles are concise and reflective. Religious elements also subtly shape symbolic choices in both traditions.The study introduces a detailed classification of riddle imagery into semantic categories and reveals how cultural context determines metaphorical depth and poetic form.These findings underscore the potential of riddles as tools for intercultural education and linguocultural pedagogy. By analyzing them as symbolic texts, educators and researchers can gain deeper insights into national identity formation and the transmission of cultural knowledge.